The Head and Neck Anatomy of Sea Turtles (Cryptodira: Chelonioidea) and Skull Shape in Testudines - Jones, Marc E. H.; Werneburg, Ingmar; Curtis, Neil; Penrose, Rod; O’Higgins, Paul; Fagan, Michael J.; Evans, Susan E. (PLOS ONE, 2012)
Background Sea turtles (Chelonoidea) are a charismatic group of marine reptiles that occupy a range of important ecological roles. However, the diversity and evolution of their feeding anatomy remain incompletely known. Methodology/Principal Findings Using computed tomography and classical comparative anatomy we describe the cranial anatomy in two sea turtles, the loggerhead (Caretta caretta) and Kemp’s ridley (Lepidochelys kempii), for a better understanding of sea turtle functional anatomy and morphological variation. In both taxa the temporal region of the skull is enclosed by bone and the jaw joint structure and muscle arrangement indicate that palinal jaw movement is possible. The tongue is relatively small, and the hyoid apparatus is not as conspicuous as in some freshwater aquatic turtles. We find several similarities between the muscles of C. caretta and L. kempii, but comparison with other turtles suggests only one of these characters may be derived: connection of the m. adductor mandibulae internus into the Pars intramandibularis via the Zwischensehne. The large fleshy origin of the m. adductor mandibulae externus Pars superficialis from the jugal seems to be a characteristic feature of sea turtles. Conclusions/Significance In C. caretta and L. kempii the ability to suction feed does not seem to be as well developed as that found in some freshwater aquatic turtles. Instead both have skulls suited to forceful biting. This is consistent with the observation that both taxa tend to feed on relatively slow moving but sometimes armoured prey. The broad fleshy origin of the m. adductor mandibulae externus Pars superficialis may be linked to thecheek region being almost fully enclosed in bone but the relationship is complex.